Evolutionary remodelling of N‐terminal domain loops fine‐tunes SARS‐CoV‐2 spike. (1st September 2022) - Cantoni, Diego; Murray, Matthew J; Kalemera, Mphatso D; Dicken, Samuel J; Stejskal, Lenka; Brown, Georgina; Lytras, Spyros; Coey, Jonathon D; McKenna, James; Bridgett, Stephen; Simpson, David; Fairley, Derek; et al.
Abstract: The emergence of SARS‐CoV‐2 variants has exacerbated the COVID‐19 global health crisis. Thus far, all variants carry mutations in the spike glycoprotein, which is a critical determinant of viral transmission being responsible for attachment, receptor engagement and membrane fusion, and an important target of immunity. Variants frequently bear truncations of flexible loops in the N‐terminal domain (NTD) of spike; the functional importance of these modifications has remained poorly characterised. We demonstrate that NTD deletions are important for efficient entry by the Alpha and Omicron variants and that this correlates with spike stability. Phylogenetic analysis reveals extensive NTD loop length polymorphisms across the sarbecoviruses, setting an evolutionary precedent for loop remodelling. Guided by these analyses, we demonstrate that variations in NTD loop length, alone, are sufficient to modulate virus entry. We propose that variations in NTD loop length act to fine‐tune spike; this may provide a mechanism for SARS‐CoV‐2 to navigate a complex selection landscape encompassing optimisation of essential functionality, immune‐driven antigenic variation and ongoing adaptation to a new host. Synopsis: The functional importance of the SARS‐CoV‐2 spike N‐terminal domain is poorly understood. This study demonstrates that length variation in flexible loops within the NTD can modulate spike activity to optimise SARS‐CoV‐2 entry. SARS‐CoV‐2 spike NTD loops are a hotspot of diversity in emergent variants and sarbecoviruses in general. The NTD determines virus entry efficiency by Alpha and Omicron variants, and by Pangolin coronavirus. NTD loops may provide a mechanism for evolutionary fine tuning of spike activity. Abstract : The functional importance of the SARS‐CoV‐2 spike N‐terminal domain is poorly understood. This study demonstrates that length variation in flexible loops within the NTD can modulate spike activity to optimise SARS‐CoV‐2 entry.